Electrochemically-promoted synthesis of benzo[b]thiophene-1, 1-dioxides via strained quaternary spirocyclization. Issue 34 (12th August 2022) - Li, Ruitao; Yuan, Dafu; Ping, Mengqi; Zhu, Yuyi; Ni, Shaofei; Li, Ming; Wen, Lirong; Zhang, Lin-Bao
Abstract : We report an approach for the synthesis of benzothiophene motifs under electrochemical conditions by the reaction of sulfonhydrazides with internal alkynes. Abstract : We report an approach for the synthesis of benzothiophene motifs under electrochemical conditions by the reaction of sulfonhydrazides with internal alkynes. Upon the formation of a quaternary spirocyclization intermediate by the selective ipso -addition instead of an ortho -attack, the S-migration process was rationalized to lead to the products. Computational studies revealed the selectivity and the compatibility of drug molecules showcased the potential application of the protocols.